2022
DOI: 10.5114/pg.2021.107801
|View full text |Cite
|
Sign up to set email alerts
|

Utility of immunohistochemical expression of E-cadherin in colorectal carcinoma

Abstract: Introduction: Reduced expression of E-cadherin, an intercellular junction protein, is associated with differentiation and metastasis of multiple cancers, including colorectal cancer.Aim: To investigate the utility of the immunohistochemistry of E-cadherin as a prognostic marker for colorectal cancer (CRC).Material and methods: Immunohistochemical analysis for E-cadherin was performed on 100 paraffin blocks retrieved from resected specimens of CRC patients. The collected data were statistically analysed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Archilla et al reported the rectum was a more common tumour site than the colon [ 21 ]. Whereas other studies by Rajkumar et al and Iseki et al reported a higher incidence in the colon, which was similar to our study [ 19 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Archilla et al reported the rectum was a more common tumour site than the colon [ 21 ]. Whereas other studies by Rajkumar et al and Iseki et al reported a higher incidence in the colon, which was similar to our study [ 19 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were similar to those from the studies by Choi et al [ 17 ] and Ngan et al [ 29 ]. Also, previous studies observed that EMT-related marker expression is linked to tumour size, differentiation, growth patterns, metastasis, and poor prognosis [ 22 ]. Ribatti et al concluded that EMT controls tumour development, progression, and metastasis in the tumour microenvironment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%